Prevalencia de desnutrición en preescolares - Cunalata Altamirano, Edwin Fabián (2020)
The present research aims to analyze the prevalence figures of malnutrition in preschoolers shown by national and international institutions. Early diagnosis is very important because it develops certain complications that can aggravate this disease, for this reason it is necessary to summarize the factors of main risk as determinants of child malnutrition and the clinical picture predominant, describe the principal causes of morbidity and mortality associated with child malnutrition in Ecuador. The research is basic, descriptive, explanatory with a mixed approach. The study population for the research was made up of all forty two scientific articles in which the subject is addressed Prevalence of Malnutrition in preschool or Child Malnutrition, published in indexed journals and world impact journals, the Scielo database, Scopus, Pubmed , Elsevier, UpTodate disclosed in the last 5 years, and in books such as: Pediatrics Nelson, Cruz's Treatise on Pediatrics. Through which 25 publications were chosen, of the 3 are located in Scopus, 8 in Scielo, 4 in Pubmed, 6 in Elsevier and 4 in UpTodate. The authors highlight that the prevalence figures for child malnutrition in the country are, They are in the highest percentages, ranking second in Latin America. Illiteracy and intestinal parasitosis play a crucial role in the development of malnutrition in Ecuador. The consequence of improper handling of the child malnutrition will be reflected in suffering of morbidities such as diabetes and cardiovascular diseases such as high blood pressure.